Upper gastrointestinal bleeding secondary to late gastric metastasis of renal cell carcinoma - Cerrella Cano, Carolina; Junquera Alonso, Eduardo; Terroba Alonso, Marina; Cáceres Pieter, Carmen Elisa; Parapar Álvarez, Leire; Soto Sánchez, Javier; Pérez Corte, Daniel (Revista española de enfermedades digestivas, 2023)
Clear cell renal cell carcinoma is the most common renal neoplasm in adults. It has a relatively slow growth pattern that delays diagnosis until the onset of local, paraneoplastic or metastasis-related manifestations, and an unpredictable behavior ranging from aggressive tumors with poor short-term prognosis to late recurrence cases where metastases are identified years after nephrectomy, the latter scenario being the subject of the case we herein report.